GAMIFICATION IN INCLUSIVE EDUCATION: IMPACTS ON EARLY CHILDHOOD EDUCATION (Editora Impacto Científico, 2025)
The present work aims to analyze the use of gamification in Early Childhood Education for children in special education at a municipal public CEIM in Lages/SC. The research's guiding question sought to understand the impacts of gamification on promoting inclusive learning for children in Early Childhood Education between 1 and 6 years old. The general objective was defined as: to identify the impacts of gamification on the teaching and learning process of the special education students in Early Childhood Education classes at a school in Lages/SC. The research has an exploratory and descriptive nature, with a qualitative approach, and the applied methodology was bibliographical and field research. The data for analysis were collected through interviews with three teachers and four parents involved in the teaching and learning of children with disabilities at the CEIM. The main results showed that, despite the significant work with gamification at the institution, there is a lack of ongoing teacher training and technological materials for the effective use of these technologies; similarly, there is a recognition by teachers and parents of the children's progress through the use of gamification methodologies. Given this reality, it is suggested that the technological organization of the school participating in this research serve as a foundation for further studies on teaching practices using gamification, aiming for a more inclusive education aligned with contemporary social demands.